Five habits of successful people / Nicole Heather Esak - Esak, Nichole Heather (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Many successful individuals have good organizational skills. These successful individuals plan everything and create priorities so they know what to accomplish in their lives, including the objective they want it reach.